Green Leaf Volatile-Burst in Selaginella moellendorffii - Tanaka, Moena; Koeduka, Takao; Matsui, Kenji (Frontiers in Plant Science, 2021)
Green leaf volatiles (GLVs) consist of six-carbon volatile aldehydes, alcohols, and their esters. They are formed from polyunsaturated fatty acids and are involved in the defense of plants against herbivores and pathogens. GLVs generally have low concentrations in intact healthy plant tissues, but the biosynthetic pathway to form GLVs is quickly activated by mechanical damage to tissues, an event called the GLV-burst. Most seed plants have the ability to implement GLV-burst; however, this potential in non-seed plants has not been extensively researched. In this study, we examined the GLV-burst capacity of monilophytes, lycophytes, and bryophytes, and confirmed that monilophytes and lycophytes showed substantial GLV-burst ability, while bryophytes did not, with a few exceptions. When the genome sequence of a model lycophyte, Selaginella moellendorffii was reviewed, ten genes were found that showed high similarity with the noncanonical cytochrome P450 enzymes, CYP74s, specialized in oxylipin formation. Recombinant proteins expressed with E. coli showed that one of them had the ability to encode allene oxide synthase, and another encoded hydroperoxide lyase (HPL), preferring linolenic acid 13-hydroperoxide, and it was inferred that this gene was responsible for GLV-burst in S. moellendorffii. Based on the phylogenetic tree constructed with CYP74s of non-seed and seed plants, we hypothesized that HPL was acquired independently in the lycophyte and seed plants through diversification of CYP74 genes.